A COMPARATIVE STUDY OF ENHANCE AND IMPROVE IN L1 AND L2 ACADEMIC WRITING - Hasibuan, Apriyanti; Oktarina, Hanifah (Esteem Journal of English Education Study Programme, 2025)
Lexical verbs like enhance and improve are crucial in academic writing, signaling change, development, and authorial stance. However, their use by native (L1) and non-native (L2) English writers remains underexplored. This comparative study investigates the frequency, grammatical patterns, and stance-related functions of these verbs in journal articles by L1 and L2 authors. Using AntConc and Partington et al.’s (2013) evaluative stance framework, the study analyzes syntactic and semantic usage. Results show that while both groups use the verbs correctly, L1 writers prefer abstract, passive, and nominalized structures that reflect disciplinary conventions and subtle evaluation. L2 writers, however, favor active constructions and concrete collocations, often linked to observable outcomes or instructional contexts. These differences reveal varied approaches to expressing stance and rhetorical positioning, suggesting that L1 writers demonstrate greater awareness of disciplinary norms. The study emphasizes the role of verb choice and syntactic form in academic identity construction and offers implications for academic writing instruction, particularly in supporting L2 writers’ engagement with disciplinary discourse.